Rab40b regulates trafficking of MMP2 and MMP9 during invadopodia formation and invasion of breast cancer cells - Jacob, Abitha (The Company of Biologists, 2013)
Invadopodia-dependent degradation of the basement membrane plays a major role during metastasis of breast cancer cells. Basement membrane degradation is mediated by targeted secretion of various matrix metalloproteinases (MMPs). Specifically, MMP2 and MMP9 (MMP2/9) possess the ability to hydrolyze components of the basement membrane and regulate various aspects of tumor growth and metastasis. However, the membrane transport machinery that mediates targeting of MMP2/9 to the invadopodia during cancer cell invasion remains to be defined. Because Rab GTPases are key regulators of membrane transport, we screened a human Rab siRNA library and identified Rab40b GTPase as a protein required for secretion of MMP2/9. We also have shown that Rab40b functions during at least two distinct steps of MMP2/9 transport. Here, we demonstrate that Rab40b is required for MMP2/9 sorting into VAMP4-containing secretory vesicles. We also show that Rab40b regulates transport of MMP2/9 secretory vesicles during invadopodia formation and is required for invadopodia-dependent extracellular matrix degradation. Finally, we demonstrate that Rab40b is also required for breast cancer cell invasion in vitro. On the basis of these findings, we propose that Rab40b mediates trafficking of MMP2/9 during invadopodia formation and metastasis of breast cancer cells.